Unintended Consequences of Linking Tax Return Disclosures to Financial Reporting for Income Taxes: Evidence from Schedule UTP - Towery, Erin M. (The Accounting Review, 2017)
ABSTRACT This study exploits the implementation of IRS Schedule UTP to examine how linking tax return disclosures to financial reporting for income taxes affects firms' reporting decisions. Using confidential tax return data and public financial statement data, I find that after imposition of Schedule UTP reporting requirements, firms report lower financial reporting reserves for uncertain income tax positions, but do not claim fewer income tax benefits on their federal tax returns. The reduction in reserves is concentrated among multinational firms and firms with larger reserves prior to Schedule UTP. These findings suggest that some firms changed their financial reporting for uncertain tax positions to avoid Schedule UTP reporting requirements without changing the underlying positions. In contrast with prior studies, this evidence represents a permanent, rather than a temporary, tax-induced reporting change. My results imply that linking tax return disclosures to financial reporting can have unintended effects on firms' reporting decisions.